Determinan konvergensi daerah di Sulawesi Selatan: Apakah variabel sosial-ekonomi berpengaruh? - Rusydi, Bahrul Ulum (Nur Science Institute, 2024)
This study analyzes the convergence phenomenon between districts/cities in South Sulawesi. In addition, this study will analyze the influence of socio-economic variables on the value of GRDP per capita, which is an indicator of regional convergence. This research is included in the type of quantitative research using secondary data, the data structure of which is panel data. The panel data consists of 10 years of observation, namely 2014 to 2023, for 24 districts/cities in South Sulawesi. Panel regression model testing using the Fixed Effect Model. The convergence phenomenon is seen using two approaches, namely sigma convergence and beta convergence, consisting of absolute and conditional convergence. The results found that the sigma convergence approach concluded a convergence between South Sulawesi regions. The analysis results with the absolute convergence method concluded that convergence occurred, and conditional convergence also found the same results. Regarding the influence of socio-economic variables, it was found that only economic variables had a significant and positive effect on GRDP per capita. This finding implies that the convergence between regions in South Sulawesi indicates that the economic development process is on the right track. In addition, it is also a direct indication of an increase in the quality of life that leads to a decrease in inter-regional inequality in South Sulawesi.